2020
DOI: 10.1186/s12961-019-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of power, context and agency in improving patient experience through a patient and family centred care approach

Abstract: Background: Research shows that the way that healthcare staff experience their job impacts on their individual performance, patient experience and outcomes as well as on the performance of organisations. This article builds on this literature by investigating, with multi-disciplinary clinical teams as well as patients and relatives, what factors help or hinder changes designed to improve patient experience. Methods: Qualitative research looking at patient-and family-centred care (PFCC) on two care pathways (st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 48 publications
2
67
0
Order By: Relevance
“…Findings of this study support previous qualitative and quantitative research conducted with healthcare providers, parents and patients (both adult and paediatric), which found that the hierarchical medical model of care is still dominant when providing care [17,21]. Participants in this study highlighted the lack of shared decision making led them to have negative experiences of care and agency [17,21]. Parents and healthcare providers both described the need to respect the expertise they each bring to the care of the child and young person with complex healthcare needs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings of this study support previous qualitative and quantitative research conducted with healthcare providers, parents and patients (both adult and paediatric), which found that the hierarchical medical model of care is still dominant when providing care [17,21]. Participants in this study highlighted the lack of shared decision making led them to have negative experiences of care and agency [17,21]. Parents and healthcare providers both described the need to respect the expertise they each bring to the care of the child and young person with complex healthcare needs.…”
Section: Discussionsupporting
confidence: 85%
“…In an integrated system, these needs are met through the coordinated and collaborative working of all providers, irrespective of sectorial, organisational or geographic boundaries." [15, p. 5] CHQHHS's definition incorporates person-centredness as a central component of integrated care, recognising that a person and their immediate family and/or carers must be empowered and engaged within the healthcare system and their own care coordination [15][16][17].…”
Section: Research and Theorymentioning
confidence: 99%
“…Calls to ensure cultural safety in the health system are embedded in Australian national health policy infrastructure (34), which also advocates robust patient experience measurement processes (35). The failure to measure patient experiences from a cultural safety perspective and the impact of the setting in which cancer care is experienced, mean that super cial information may be gathered, rather than information that may be at the core of an Indigenous person's (dis)engagement with treatment (4,5). As cultural safety is determined by the patient and family (32,34,35), the development of indicators which come from a cultural safety perspective is likely to contribute to greater relevance of patient experience measures for Indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported experiences are routinely used as a key indicator of the quality of health care, along with patient-reported outcome measures, safety measures and clinical outcomes (1)(2)(3). However, there are concerns that many mechanisms used to collect patient experience data produce large amounts of super cial data, while missing deeper, more nuanced information that is meaningful to the patient (4,5), and that insu cient attention is paid to whether the information is used to inform health care provision (6,7). In addition, gaps have been identi ed in understanding the experiences of underserved groups, whose interactions with health services may be markedly different to general patient populations (8).…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least, physiotherapists’ success in implementing fall-prevention programmes and interventions depend on empowering leadership and a working culture, along with time and multifaceted professional competence [ 38 ]. Furthermore, research indicate that clinicians’ experience might contribute to strategic priorities to improve patient experience and place patients at the centre of healthcare and decision-making [ 39 ].…”
Section: Introductionmentioning
confidence: 99%